Accountability and social responsibility international perspectives - Crowther, David; Lauesen, Linne Marie (Developments in corporate governance and responsibility ;, 2016)
Probably since the mid-1980s, corporate governance has attracted a great deal of attention from corporate managers and investors protection has become a much more important issue for all financial markets after recent firm failures and scandals. Especially important for all with an interest in how organizational governance is formed around socially responsible and accountable ways of leadership and management, this book provides new insights into various issues regarding business management and governance, and points to ways for businesses to make a real change for the betterment of the world, especially in the aftermath of the recent financial crisis 2007/2008.